Systemic functional grammar in natural language generation : linguistic description and computational representation - Teich, Elke. (London : Cassell, 1999)
This book is divided into six parts: Introduction; Theory and linguistic representation: systemic functional linguistics; Computational application; Description; Computational representation; Summary and Conclusion.
Keywords: Computational linguistics; Systemic grammar; Dependency grammar; Computational linguistics; Systemic grammar; Dependency grammar